MORPHOBIOLOGY AND BIOCHEMICAL VALUE OF LYCHEE PLANT (LITCHI CHINENSIS) (American Journal of Interdisciplinary Research and Development, 2022)
This article provides valuable scientific information about the Chinese lychee plant (Litchi chinensis) in folk medicine, origin and distribution area, medicinal properties, and cultivation technology.